The effect of walnut (tetracarpidium conophorum) leaf and onion (allium cepa) bulb residues on the growth performance and nutrient utlization of clarias gariepinus juveniles (2012)
Feeding trial were conducted in experimental tanks (50 x 34 x 27 cm) to assess the growth responses and nutrient utilization of Walnut Leaf (WL) and Onion Bulb (OB) residues in Clarias gariepinus. Nine experimental diets: control (0%), OB2 (0.5%), OB3 (1.0%), OB4 (1.5%), OB5 (2.0%), WL6 (0.5%), WL7 (1.0%), WL8 (1.5%) and WL9 (2.0%) were formulated and replicated thrice at 40% crude protein. Fish (mean weight 7.39±0.02 g and length 10.37±1.24 cm) were fed twice daily at 3% body weight for 12 weeks. Mean Weight Gain (MWG), Specific Growth Rate (SGR) and Feed Conversion Ratio (FCR) were measured. Temperature, dissolved oxygen and pH were determined using standard methods and economic analysis was investigated. Data were analyzed using descriptive statistics and ANOVA at p=0.05. Results showed that the Fish on OB and WL residue- based diets had higher growth than those on control diet but C. gariepinus fed WL8 had significantly higher MWG, SGR and FCR of 53.81±1.20 g, 1.09±0.11 g and 2.16±0.01 respectively of all treatments. The values of temperature, dissolved oxygen and pH were closely related and were still within the range for fish culture in the tropics. WL8 had higher profit index (1.40) and incidence of cost (0.032) and the least in OB5 (1.18) (0.039) respectively. These suggest that walnut leaf residue at 1.5% inclusion could be a potential, less expensive and promising dietary supplementation than onion bulb residue and control that would positively affect growth and water quality of Clarias gariepinus in aquaculture